EFFECT OF DIFFERENT TYPES OF FERTILIZER ON THE GROWTH OF MARINE PHYTOPLANKTON POPULATION Chlorella vulgaris - Fauzan, M.; Siregar, Sofyan Husein; Nasution, Syafruddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
This research was conducted on October 13-26, 2019 in the Regional Technical Implementation Unit of the Seawater and Brackish Aquaculture Fisheries Office (UPTD BPBALP Teluk Buo), West Sumatra. This study aims to determine the effect of applying different types of fertilizers to the growth of Chlorella vulgaris microalgae populations on laboratory scale culture. The method used in this study was an experimental method in the laboratory using a completely randomized design (CRD) one factor, namely the difference in fertilizer types with 3 (three) replications. Fertilizers used are Walne fertilizer, ZA (Zwavelzure Ammoniak) and TSP (Triple Super Phosphate). The testing organism in this study was phytoplankton C. vulgaris. The container used was a glass jar (3 liter capacity). The parameters measured in this study include absolute growth, relative growth, specific growth, self-doubling time and water quality. The results of this study indicate that the best type of fertilizer for C.vulgaris population growth was TSP fertilizer, followed by ZA fertilizer and the lowest in Walne fertilizer.